Social Distancing and Lockdown – An Introvert’s Paradise? An Empirical Investigation on the Association Between Introversion and the Psychological Impact of COVID19-Related Circumstantial Changes - Wei, Maryann (Frontiers in Psychology, 2020)
The coronavirus disease 2019 (COVID19) pandemic has effected the implementation of social distancing and lockdown measures across the globe, and the psychological impact of associated life changes is experienced more severely by some individuals than others. Anecdotal evidence points to a common belief among the general public that introverts are faring better than their extraverted counterparts to this end. However, the claim lacks empirical research, and seems counterintuitive when the broader literature on the association between introversion and mental health is considered. The current study investigated whether the psychological impact of COVID19-related circumstantial changes was moderated by introversion, based on outcome measures across psychosocial, cognitive, and affective domains. The role of several demographic factors in determining COVID19-related mental health symptoms was also examined. 114 individuals (64 USA residents) completed measures of introversion, and reported on the extent to which they experienced loneliness, anxiety, depression and cognitive impairments as a function of COVID19-related circumstantial changes. Results showed that introversion predicted more severe loneliness, anxiety, and depression experienced as a function of COVID19-related circumstantial changes, but not cognitive impairments. Among the range of demographic factors examined (age, gender, living condition, recent unemployment), living with others (vs. living alone) predicted more severe COVID19-related mental health symptoms. However, these effects were only observed on outcome measures pertaining to anxiety and cognitive impairments, but not loneliness and depression. Current findings have implications for both consumers and disseminators of information on popular internet hubs. Current findings also highlight the possibility that living with others (close human affiliation) may have protective and detrimental effects on different domains of mental health during the COVID19 pandemic.